The Role of Social Networks as Survival Strategies in Agro-Pastoral Communities in Arid And Semi-Arid Lands in Tanzania - Rusomyo, Rematus; Junlin, He; Mangare, Catherine (Asian Development Policy Review, 2017)
Agro-pastoral communities in semi-arid areas of Tanzania are among the most food insecure groups in the country. In the absence of precisely stipulated mitigation measures from the government the agro-pastoralists have, all across their history relied on social networks for their survival. This paper seeks to examine in detail the role of social networks as survival strategies in coping up with food insecurity among agro-pastoral communities in Arid and semi-arid areas of Tanzania. Based on data and information that was collected through focus group discussions and in-depth interviews in three villages of Sejeli, Mtumba and Makoja it is reported that social networks have been significant in sustaining livelihoods of vulnerable households. These traditional social networks are based on mutual trust and organized on consanguine and kinship ties and through these networks wealth and riches are shared by the agro-pastoral communities. The findings further reveal that these traditional social networks do better than the externally induced initiatives. It has also been revealed that, despite facing a myriad of challenges such as competition for labor, lack of entrepreneurial skills and negative impacts of commercialization of livelihoods on food security the traditional social networks are surviving albeit with hitches. It is recommended that policy interventions that seek to construct resilience of the vulnerable households need to consider traditional systems of social networking.